2009
DOI: 10.1140/epjc/s10052-009-1118-8
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraint on generalized Chaplygin gas model

Abstract: We investigate observational constraints on the generalized Chaplygin gas (GCG) model as the unification of dark matter and dark energy from the latest observational data: the Union SNe Ia data, the observational Hubble data, the SDSS baryon acoustic peak and the fiveyear WMAP shift parameter. The result is obtained that the best-fit values of the GCG model parameters with their confidence level are A s = 0.73 (2σ ). Furthermore, in this model, we can see that the evolution of equation of state (EOS) for dark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 68 publications
5
49
0
Order By: Relevance
“…As a competitive model to explain the lately accelerated expansion of universe, a unified dark fluid (UDF) model [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] was investigated extensively in the recent years. The striking features of the UDF model are that it combines cold dark matter and dark energy and that it behaves like the cold dark matter and the dark energy at an early epoch and a late time, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As a competitive model to explain the lately accelerated expansion of universe, a unified dark fluid (UDF) model [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] was investigated extensively in the recent years. The striking features of the UDF model are that it combines cold dark matter and dark energy and that it behaves like the cold dark matter and the dark energy at an early epoch and a late time, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called general Chaplygin gas model (GCG) has been widely studied to explain the accelerating Universe [21,22,50]. In the GCG model, the dark sectors in the Universe, i.e., dark energy and dark matter, can be unified through an exotic equation of state.…”
Section: Gcg Modelmentioning
confidence: 99%
“…In particular, Scherrer (2006) discussed GCG model with the parameter α > 0 and obtained w < 3w(1 + w) in the w-w plane. However, the latest observational data has given the best fit value α = −0.09 +0.26 −0.19 at 95% confidence level (Lu et al 2009) for GCG model in a flat universe which has shown α < 0 is very possible. In this paper, we have extended the range of the parameter α to −0.28 < α < 0 and found 3w(1 + w) < w < w(1 + w) which satisfies the limit derived in Caldwell and Linder (2005) for "freezing" quintessence model.…”
Section: Introductionmentioning
confidence: 98%